Hubungan Konsumsi Junk Food dan Kebiasaan Tidur dengan Status Gizi Siswa SMP di Surabaya - Nikmatul Islamiah; Faridha Nurhayati (MAN Insan Cendekia Jambi, 2026)
The purpose of this study is to examine the relationship between junk food consumption and sleep habits with the nutritional status of students at SMPN 35 Surabaya. The research method used is a correlational approach with an Ex Post Facto design. The research sample was obtained using a cluster random sampling method, resulting in 257 respondents, consisting of 132 males and 125 females. The research instrument was a structured questionnaire that had undergone a validity test, with 23 statements declared valid (r-count ≥ r-table 0.1224), and a reliability test with a Cronbach's Alpha value of 0.576. Nutritional status was determined using BMI/age standards. The data were analyzed using descriptive statistics and the Chi-Square test, and processed with the help of SPSS software. The results of the study indicate a significant relationship between junk food consumption and the nutritional status of students at SMPN 35 Surabaya (p=0.005 < 0.05). In contrast, sleep habits showed no significant association (p=0.178 > 0.05). The conclusion of this study is that junk food consumption more dominantly affects students' nutritional status than sleep habits. These results can help schools in making healthy canteen policies and provide nutrition education for students and parents.